PENGARUH MOTIVASI KERJA, BUDAYA DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA PADA PEGAWAI PERWAKILAN BKKBN PROVINSI SULAWESI TENGGARA : Studi Pada Perwakilan BKKBN Provinsi Sulawesi Tenggara - Rahmania Elvinasari; Nursaban Rommy Suleman; La Ode Asfahyadin Aliddin; La Hatani; Nasrul Nasrul; Wahyuniati Hamid (Pascasarjana Universitas Halu Oleo, 2021)
The purpose of this study was to examine and explain the effect of work motivation, culture and organizational commitment on job satisfaction of employees of the BKKBN Representative in Southeast Sulawesi Province. This research design is based on a quantitative approach with a positivist paradigm through a survey method. Data was collected in a cross-sectional manner using an instrument in the form of a questionnaire to all employees of the BKKBN Priovinsi Southeast Sulawesi Representative Employees as many as 57 people. The analytical tool used in testing the hypothesis of this research is multivariate regression analysis.The results showed that work motivation has a positive and significant effect on job satisfaction, organizational culture has a positive and significant effect on job satisfaction, good organizational commitment has been proven to have a positive and significant contribution to increasing employee job satisfaction. Finally, work motivation, organizational culture and organizational commitment have a significant simultaneous effect on employee job satisfaction. Thus, it can be concluded that changes in increasing work motivation which are reflected through the need for achievement, bureaucratic culture and affective commitment have a positive and significant contribution together to job satisfaction through job satisfaction, incentives/bonuses and benefits, working conditions and co-workers.